Content analysis of English textbooks for tenth grade of senior high school - Ida Vinny Sudaningsih; Imam Ghozali (Journal of English Language and Pedagogy, 2020)
The objectives of this study are to (1) discover whether or not the English textbooks for tenth grade fulfilled the criteria of a good textbook by Alan Cunningsworth, and (2) find out the strengths and weaknesses of the three textbooks used by tenth-grade students Senior High School. This research was conducted using content analysis because the data were collected from the content of textbooks. The object of this research was three textbooks. They are Talk Active, Pathway to English, and Bahasa Inggris for the tenth-grade senior high school. The research adapted Cunningsworth’s theory of a good textbook to evaluate these textbooks. The data were taken from document analysis and interview. The steps of the research were data collection, data reduction, data display, and giving a conclusion. The results of this research were (1) Talk Active fulfils four criteria of a good textbook by Cunningsworth; they are aims and approaches, topic, methodology, and political consideration. Pathway to English meets six criteria by Cunningsworth; aims and approaches, design and organization, topic, methodology, teachers’ book, and political consideration. Bahasa Inggris meets five criteria by Cunningsworth; aims and approaches, design and organization, topic, teachers’ book, and political consideration. (2) The strengths of Talk Active are in terms of appearance, activities, and materials. Pathway to English has strengths in terms of topics, activities, social and cultural context, and media. Bahasa Inggris has strengths in terms of activities, appearance, and communicative competence. On the other hand, Talk Active contains some weaknesses in terms of authentic language and content. Pathway to English present unattractive colouring, limited vocabulary, an expensive price, then Bahasa Inggris has weaknesses in terms of complete materials, less social and cultural context. It does not cover four basic skills in English.